Supraregional agglomeration economies and regional clubs - Antonio Jose Mora (European Regional Science Association (ERSA), 1998)
Recently there have appeared considerable number of papers concerning the idea that externalities affect growth and its dynamics. This paper determines the importance of these external effects to the estimatiom and analysis of an output function. We have observed this fact for the Spanish case at the regional level. The relation of factors in a production function becomes altered by external facts. We estimate the relevance of externalities in this function and try to identify their sources. Convergence or divergence and its rate depend on the existence of regional externalities. Considering the idea that regional economies could be optimally grouped (groups showing the highest levels of homogeneity), there is evidence that these groups are not randomly located in the space. Then, this question naturally arises: Could it be due to the presence of regional externalities? If economic activity is conditioned by regional externalities, the location decision of a firm will be influence by those externalities. This point would be related to the existence of supraregional agglomeration economies. Furthermore, we evaluate the presence and intensity of the sources of such externalities in each group of regions and the possibility of difference sources in different groups.
Keywords: 330